Odpowiedzi

2010-01-04T20:29:34+01:00
(10x+y)-(10y+x)=45
10x+10y=90

10x+y-10y-x=45
x+y=9

x=9-y
81-9y-9y=45

x=9y
-18y=-36

y=2
x=7




(10x+y)+3y=44
(10y+x)-5x=52

10x+4y=44
10y-4x=52

10x+4y=44
25y-10x=130

29y=174
10x+4y=44

y=6
x=2




2010-01-04T20:37:11+01:00
(10x+y)-(10y+x)=45
10x+10y=90 /:10

10x+y-10y-x=45
x+y=9

9x-9y=45
x=9-y

9*(9-y)-9y=45
x=9-y

81-9y-9y=45
x=9-y

-18y=-36 /:(-18)
x=9-y

y=2
x=9-2

y=2
x=7

Odp. Rozwiązaniem układu równań jest para liczb y=2 i x=7.

(10x+y)+3y=44
(10y+x)-5x=52

10x+y+3y=44
10y+x-5x=52

10x+3y=44 /*2
10y-4x=52 /*5

20x+6y=88
50y-20x=260
___________
56y=348 /:56
y=6

y=6
20x+6*6=88

y=6
20x=52 /:20

y=6
x=2,6

Odp. Rozwiązaniem układu równań jest para liczb y=6 i x=2,6.